The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adhm.202001916
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymer for Implantable Electronics toward Clinical Application

Abstract: Owing to their excellent mechanical flexibility, mixed‐conducting electrical property, and extraordinary chemical turnability, conjugated polymers have been demonstrated to be an ideal bioelectronic interface to deliver therapeutic effect in many different chronic diseases. This review article summarizes the latest advances in implantable electronics using conjugated polymers as electroactive materials and identifies remaining challenges and opportunities for developing electronic medicine. Examples of conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 120 publications
0
47
0
Order By: Relevance
“…[82] Conducting polymers exhibit attractive properties, such as mixed ionic-electronic conductivity, leading to low interfacial impedance, tunability by chemical synthesis, solution process ability and biomechanical compatibility with living tissues, which makes them ideal materials for bioelectronics and stretchable electronics. [83][84][85] However, they show typically poor mechanical properties and are therefore not suitable as self-healing materials. [86][87][88][89][90] Self-healing conductors can be achieved upon mixing with other polymers, such as poly(vinyl alcohol) (PVA) and poly(ethylene glycol) (PEG), which provide the mechanical characteristics leading to self-healing.…”
Section: Introduction To Organic Conducting Polymersmentioning
confidence: 99%
“…[82] Conducting polymers exhibit attractive properties, such as mixed ionic-electronic conductivity, leading to low interfacial impedance, tunability by chemical synthesis, solution process ability and biomechanical compatibility with living tissues, which makes them ideal materials for bioelectronics and stretchable electronics. [83][84][85] However, they show typically poor mechanical properties and are therefore not suitable as self-healing materials. [86][87][88][89][90] Self-healing conductors can be achieved upon mixing with other polymers, such as poly(vinyl alcohol) (PVA) and poly(ethylene glycol) (PEG), which provide the mechanical characteristics leading to self-healing.…”
Section: Introduction To Organic Conducting Polymersmentioning
confidence: 99%
“…[3] Soft bioelectronics were developed in recent years to replace the rigid components in traditional bioelectronics with tissue-like soft materials to improve the conformability and reduce the adverse immune responses, [4,5] and this area asks for high-performance soft conductors to realize the functionalities of such tissue-like bioelectronics.Conducting polymer hydrogels are promising conductors that can serve as the electrodes for soft bioelectronics. [6,7] Hydrogels are water-rich networks that present high biocompatibility, tissuelike mechanical properties, and tunable functionalities desired for bioelectronics. [8,9] However, it is a great challenge for a conducting polymer hydrogel to achieve both high conductivity and large stretchability.…”
mentioning
confidence: 99%
“…Conducting polymer hydrogels are promising conductors that can serve as the electrodes for soft bioelectronics. [6,7] Hydrogels are water-rich networks that present high biocompatibility, tissuelike mechanical properties, and tunable functionalities desired for bioelectronics. [8,9] However, it is a great challenge for a conducting polymer hydrogel to achieve both high conductivity and large stretchability.…”
mentioning
confidence: 99%
“…Conductive polymers continue to be an active research topic for biomaterials and have demonstrated record tensile strains (>100%), low moduli (kPa-MPa), and conductivity (10 1 -10 4 S m -1 ), [578][579][580][581][582] among other tunable charac teristics such as anisotropy, [583] adhesiveness, [156,[584][585][586] and bio degradability. [587] A wide range of polymers are being explored as stretchable semiconductors, optimizing for charge car rier mobility, [587][588][589] device density, [590] ionic transport, [591] and neuromorphic computing.…”
Section: Other Conductorsmentioning
confidence: 99%